THE ZIRCON CHRONOLOGY OF THE INTRUSIVE MAGMATISM OF THE KANIN PENINSULA - V. L. ANDREICHEV; A. A. SOBOLEVA; S. A. SERGEEV; S. L. PRESNYAKOV (Известия высших учебных заведений: Геология и разведка, 2018)
The Kanin Peninsula is an elevated block of the Timan Ridge where Precambrian sedimentary-metamorphic sequences and magmatic  rocks, intruding them, form the Kanin Kamen Ridge. In the  northwestern part of the Peninsula on the coast of the Barents Sea,  there is a unique outcrop of two-mica granites, monzonitoids and  lamprophyres cutting metaterrigenous rocks of the Upper Riphean  Tabuyev series and overlain by Lower Permian limestones. To establish the age of magmatic rocks, U-Pb dating of zircons has been carried out by secondary ion mass spectrometry (SIMS) method. In  zircons from granites, an age of 883 ± 16 Ma has been obtained,  which corresponds to the beginning of the Late Riphean, and the  subsynchronous formation of subalkaline rocks occurred in the Late  Cambrian. The age of monzogabbro is 505 ± 7 Ma, and  lamprophyres – 504±7Ma.